THE RESEARCH OF MICROBIOLOGICAL INDICATORS OF WORT EXTRACTED FROM SWEET SORGHUM AND APPLE CONCENTRATE AS RAW MATERIALS IN THE PRODUCTION OF SAFE FOODSTUFFS - Карпутіна, М.В.; Вітряк, О.П.; Олійник, С.І.; Романова, З.М.; Харгелія, Д.Д.; Тетеріна, C.І. (SWorldJournal, 2022)
The microbiological and physicochemical indicators of sweet sorghum juice and unpasteurized wort based on it with the use of diluted apple concentrate were studied. The content of the main groups of microorganisms in the samples of juice and wort, which a